(untitled) (Malay Literature, 2011)
Khotbah di Atas Bukit (Sermon on a Hill) by Kuntowijoyo was written to foreground transcendental principles, in accordance with the Theory of Transcendental Literature. Transcendental principles are brought to the fore and applied in this work through the use of symbolism. Kuntowijoyo uses a local subject for enquiry, kejawen (Javanese sufism), to address issues of faith and tauhid (Islamic Monotheism or the Oneness of Allah). However, there is some ambiguity in the text which could affect the aspects of tauhid discussed. In presenting the teachings of Sufism, Kuntowijoyo may in the process be misunderstood and consequently considered to subscribe to global theology where tauhid is simplified and religions "combined". Khotbah di Atas Bukit is a complex work to read because of the overuse of symbolism aimed at obscuring meaning. This kind of symbolism needs to be explained, particularly to readers who have little knowledge of sufism. It is this that makes Khotbah di Atas Bukit a specialized work for a specialized readership. Key words: Islamic literature, Islam kejawen, sufism, perennial philosophy, Islamic leadership, tauhid, Kuntowijoyo, pluralism, mysticism, Transcendental Literature, myth, global religion, orthodox Muslims (the faithful).